Challenges of Assisted Reproductive Technology during COVID19 Pandemic; a Letter to Editor - Aliakbari, Fereshteh; Hosseini, Mohammadreza; Sharifian, Rayka (Archives of Men's Health, 2020)
The coronavirus has spread rapidly all over the world and has become a worldwide crisis. On 11th March, 2020, the World Health Organization (WHO) described the coronavirus disease as a global pandemic. Following the mortality due to COVID-19 infection, many healthcare systems have been affected in many countries. On July 11th, 2020, 12322395 confirmed cases of coronavirus were reported, of which 556335 led to death (1) .